Observations of Deep Current at the Western Boundary of the Northern Philippine Basin - Zhou, Chun (Sci Rep, 2018)
One-year time series of current velocities and hydrographic parameters based on four deep moorings deployed east of the Luzon Strait are employed to study the deep current at the western boundary (DCWB) of the northern Philippine Basin. While the mean current is relatively weak, the DCWB is highly variable on an intraseasonal time scale, with dominant periods ranging between 30 and 80 days. During the period of observation (October 2011–October 2012), the DCWB reversed its direction at early April, and pointed southward (−2.4 cm/s) in summer/autumn and northward (1.7 cm/s) in winter/spring. This annual reversal of the DCWB is consistent with the water property distribution in the deep Philippine Basin, with relatively cold and fresh water to the north and relatively warm and salty water to the south. The moored time series also allow for discussion on the stratification of the deep Luzon Strait, which indicates the lower interface of Pacific deep water capable of furnishing the deepwater overflow in the Luzon Strait.